Renal Functional Status of Asphyxiated Babies & its Correlation with Apgar Score (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Introduction: Kidney is the 2nd commonest affected organ as a consequence of asphyxia1. Most attention is given to prevent CNS damage and neurological sequel but hypoxic renal insult not only influences neonatal morbidity & mortality but may give rise to CKD. to assess the renal functional status of asphyxiated babies.Material & Methods: This cross sectional study was conducted in the Department of Neonatology & Department of Gynecology and Obstetrics, Dhaka Medical College Hospital during January 2012 to January 2013. A total of 150 inborn, term asphyxiated neonates with e 2.5 kg who had history of delayed or no cry with Apgar score